(untitled) (Bangladesh Journal of Zoology, 2013)
The present study was carried out over a total of 330 suspected outdoor TB patients from the Shyamoli Chest Clinic, Dhaka. The prevalence of TB was 29.69%, male and female ratio for the prevalence being 2.4:1. The highest prevalence (18.37%) was observed among the 20-24 age group followed by 25-29 age group (17.35%). Prevalence of pulmonary tuberculosis (PTB) among the total cases was 74.51%; on the other hand, extra-pulmonary tuberculosis (EPTB) was 25.51%. According to the severity of 73 PTB cases, 52.05% had severe pulmonary infection, 28.8% moderate pulmonary infection, and 19.2% mild TB infection. Among 98 TB positive cases, 14.29% had relapse cases and 85.71% had new cases. Among the 14 relapse cases, 85.71% patients had PTB while 14.29% patients had EPTB. On the other hand, out of 84 new cases, 72.62% had PTB and 27.38% had EPTB. According to occupation, the highest prevalence (21.43%) was observed among service holders, followed by garments workers and laborers (17.35%). The lowest prevalence (9.18%) was found among unemployed people. The higher prevalence of TB was mostly associated with poor socio-economic condition, close contact with infected cases, illiteracy, gender related factors and health care. DOI: http://dx.doi.org/10.3329/bjz.v40i2.14315 Bangladesh J. Zool. 40(2): 213-220, 2012